Law in a hyperconnected world: Joining the dots for sustainable futures - LIM, Michelle (Institutional Knowledge at Singapore Management University, 2024)
We live in a hyperconnected world. Ecosystems and societies are linked across vast distances like never before. The unprecedented movement of people, goods and products and the transfer of capital and information characterise not only the present but also the conceivable future. Use of the term ‘hyperconnected world’ started to gain traction in the literature towards the turn of this millennium. Mainstreaming of the internet across societies led to the exploration of global hyperconnectivity across a range of spheres including business, investment and computing. The term gained further prominence with its use by the World Economic Forum in the early 2010s to describe, in particular, economic considerations in a digital age. Acknowledging that global linkages occur not only across societies and economies but also in interaction with the biophysical processes of our planet, we understand hyperconnectivity in this special issue through the lens of telecoupling. Here, ‘tele-’ denotes phenomena that occur across long distances. ‘Coupling’ refers to human and ecological systems being so closely linked that it makes no sense to consider them separately. Telecoupling therefore considers the inextricable nature of intertwined social-ecological systems and the interactions between these systems across vast time, space and governance scales. In other words, telecoupling has at its core an understanding of complex systems. That is, not only that human and ecological components of the system are inextricably interlinked but also that perturbations to one part of the system create a ripple effect of continuous feedbacks throughout the system through a network of relationships.